Assessment of the Hong Kong Liver Cancer Staging System in Europe. (21st January 2016) - Kolly, Philippe; Reeves, Helen; Sangro, Bruno; Knöpfli, Marina; Candinas, Daniel; Dufour, Jean‐François
Abstract: Background & Aims: European and American guidelines have endorsed the Barcelona Clinic Liver Cancer (BCLC) staging system. The aim of this study was to assess the performance of the recently developed Hong Kong Liver Cancer (HKLC) classification as a staging system for hepatocellular carcinoma (HCC) in Europe. Methods: We used a pooled set of 1693 HCC patients combining three prospective European cohorts. Discrimination ability between the nine substages and five stages of the HKLC classification system was assessed. To evaluate the predictive power of the HKLC and BCLC staging systems on overall survival, Nagelkerke pseudo R2, Bayesian Information Criterion and Harrell's concordance index were calculated. The number of patients who would benefit from a curative therapy was assessed for both staging systems. Results: The HKLC classification in nine substages shows suboptimal discrimination between the staging groups. The classification in five stages shows better discrimination between groups. However, the BCLC classification performs better than the HKLC classification in the ability to predict overall survival (OS). The HKLC treatment algorithm tags significantly more patients to curative therapy than the BCLC. Conclusions: The BCLC staging system performs better for European patients than the HKLC staging system in predicting OS. Twice more patients are eligible for a curative therapy with the HKLC algorithm; whether this translates in survival benefit remains to be investigated.